Microbiomes, diet flexibility, and the spread of a beetle parasite of honey bees - Huang, Qiang; Han, Wensu; Posada-Florez, Francisco; Evans, Jay D. (Frontiers in Microbiology, 2024)
Invasive pests may disturb and destructively reformat the local ecosystem. The small hive beetle (SHB), Aethina tumida, originated in Africa and has expanded to America, Australia, Europe, and Asia. A key factor facilitating its fast global expansion is its ability to subsist on diverse foods inside and outside honey bee colonies. SHBs feed on various plant fruits and exudates in the environment while searching for bee hives. After sneaking into a bee hive, they switch their diet to honey, pollen, and bee larvae. How SHBs survive on such a broad range of food remains unclear. In this study, we simulated the outside and within hive stages by providing banana and hive resources and quantified the SHB associated microbes adjusted by the diet. We found that SHBs fed on bananas were colonized by microbes coding more carbohydrateactive enzymes and a higher alpha diversity than communities from SHBs feeding on hive products or those collected directly from bee hives. SHBs fed on bananas and those collected from the hive showed high symbiont variance, indicated by the beta diversity. Surprisingly, we found the honey bee core symbiont Snodgrassella alvi in the guts of SHBs collected in bee hives. To determine the role of S. alvi in SHB biology, we inoculated SHBs with a genetically tagged culture of S. alvi, showing that this symbiont is a likely transient of SHBs. In contrast, the fungus Kodamaea ohmeri is the primary commensal of SHBs.Diet-based microbiome shifts are likely to play a key role in the spread and success of SHBs.